Natural Products Sulforaphane and Brusatol Modulate NRF2 in Bovine Mammary Cells. (29th May 2020) - Ford, Hunter; Busato, Sebastiano; Bionaz, Massimo
Abstract: Objectives: The objectives were to analyze the effect of the natural isothiocyanate sulforaphane, an agonist of NRF2, and the natural quassinoid brusatol, an NRF2 antagonist, on modulation of NRF2 in bovine mammary cells. The effects of each compound were analyzed in both serum from dairy cows before and after parturition as well as DMEM in order to better estimate in vivo effects. Given the heightened levels of oxidative stress experienced by high-producing dairy cattle, a better understanding the role of NRF2 in these animals and natural products that may modulate it is needed. Methods: Immortalized bovine mammary cells (MACT) were transfected with a luminescent gene reporter for NRF2 and cultured in media or serum collected from cows before (−29 ± 2 days relative to calving) or after parturition (7 ± 0 days relative to calving). In addition, cells were treated with either sulforaphane (SFN) or brusatol (BRU) in a series of concentrations for 24 hours in order to analyze the response of NRF2. NRF2 modulation was measured via a luciferase reporter assay. Cell viability and toxicity were also assessed using fluorescent dyes. Results: Treatment of MACT cells grown in either DMEM or serum with SFN resulted in significant NRF2 activation, but with cytotoxic effects seen as dose increased. At both 5 µ M and 10 µ M, treatment with SFN resulted in significant activation of NRF2 ( P  < 0.001), but with significant cytotoxicity at 10 µ M and above. Both NRF2 activation and cytotoxicity were reduced in the presence of serum, with significant activation of NRF2 happening at 30 µ M and cytotoxicity being significantly reduced in comparison to treatments performed in DMEM. BRU was observed to be an effective NRF2 inhibitor, with the greatest levels of inhibition occurring at 100 nM ( P  < 0.005) in all growth medias. Comparisons between BRU treatments performed in serum and DMEM are inconclusive, with no apparent differences in NRF2 inhibition, but with significant differences in cytotoxicity ( P  < 0.001), with prepartum serum having the strongest protective effect. Conclusions: SFN and BRU, can modulate NRF2 in bovine mammary cells in vitro but are potentially cytotoxic at higher doses. Additionally, culturing and treatment of cells in serum as opposed to DMEM resulted in improvements in cell viability while also affecting NRF2 activation by SFN. Funding Sources: Agricultural Research Foundation 2019–2021.